Two new species of whip spider (Amblypygi): an epigean and a cave dwelling Charinus Simon, 1892 from Belize - Miranda, Gustavo Silva De; Giupponi, Alessandro Ponce De Leão; Wizen, Gil (Zootaxa, 2016)
Central America is rich in whip spider species, mainly of the genera Phrynus and Paraphrynus (Phrynidae), but also includes few registers of Charinus (Charinidae) with no description of taxa. In this paper two new species of Charinus from Belize are described and illustrated (Charinus belizensis sp. nov. and Charinus reddelli sp. nov.) being the first species named from Central America. New records of Charinus victori Armas, 2010 from Puerto Rico, a comparative table listing the differential characters of the Caribbean and Central American species, and a distributional map of those species are also provided.